Embryological evidence of a new type of seromucous labial gland in neotropical snail-eating snakes of the genus Sibynornorphus - Oliveira, Leonardo de [UNESP]; Guerra-Fuentes, Ricardo Arturo; Zaher, Hussam (Elsevier B.V., 2017)
Snail-eating dipsadine snakes of the genera Sibynomorphus and Dipsas share infralabial glands divided into a distinct lateral portion along the lower lip (ill) and a ventrolateral portion along the mandible (i12). While ill is constituted by several small and individual glands with their short ducts opening along the margin of the lower lip, i12 is constituted by a single hypertrophied gland with a single duct that opens laterally at the level of the intermandibular raphe. This unique condition seems to be restricted to the goo-eating dipsadine snakes. Here, we describe the embryonic development of the labial glands in the goo-eating dipsadine snakes Sibynomorphus mikanii and S. neuwiedi. Our results indicate that i12 developed independently from ill, being formed through a hypertrophied invagination instead of deriving from several small independent invaginations, as is the case for ill. Additionally, il2 showed a distinct timing of development, starting in younger embryological stages, prior to the development of ill and other labial glands. The pattern of embryonic development observed for il2 supports the hypothesis that this gland evolved separately from the infralabial glands in both Sibynomorphus and Dipsas, as a novel, independent protein-secretion system associated with their specialized feeding behaviors. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Dipsadinae; Dipsas; Goo-eaters; Supralabial glands; Infralabial glands; Glandular laminae